Thermal runaway protection film

KR103024521B1Active Publication Date: 2026-09-29IND FOUND OF CHONNAM NAT UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020230161040
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-11-20
Publication Date
2026-09-29
Estimated Expiration
2043-11-20

Smart Images

  • Figure 112023128988342-PAT00001_ABST
    Figure 112023128988342-PAT00001_ABST
Patent Text Reader

Abstract

The present invention relates to a thermal runaway prevention film comprising high-purity crystalline fibers by an evaporative drying method in which an ionic molten solution of an alkali halide compound or a halide is evaporated and dried by heating while continuously passing it through a support. According to the present invention, safety in the use of a lithium secondary battery can be ensured by blocking the further propagation of flames in the event of a fire occurring during the use of the secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a thermal runaway prevention film that performs a self-extinguishing function during thermal runaway in an energy storage system (ESS) and an electric vehicle battery, and more specifically, to a thermal runaway prevention film utilizing phase-transition crystalline fibers that absorb runaway heat to prevent thermal runaway. Background Technology

[0003] Secondary batteries, such as lithium-ion batteries used in Energy Storage Systems (ESS) and electric vehicles, are a core driving force for future industries, and countries are competitively focusing on their development.

[0004] In secondary batteries, thermal runaway reaching approximately 600 to 900°C can occur in situations such as when some battery cells stop functioning, when some battery cells explode due to external impact, or when the battery is overcharged, over-discharged, or left at high temperatures. If thermal runaway occurs in any one of the battery cells, the heat propagates to adjacent battery cells or battery modules within a short period of time, eventually causing the fire to spread to the entire battery module and burn down the vehicle.

[0005] To prevent thermal runaway of a secondary battery, Korean Patent Publication No. 2017-0005117 discloses a lithium-ion battery having a thermal runaway protector comprising an endothermic material composed of aluminum foam, ceramic, ceramic fiber, or plastic, and Korean Patent No. 2332128 discloses a battery pack comprising a silicone sponge pad containing a platinum-based flame retardant.

[0006] However, there are practical limitations to preventing thermal runaway by lowering a temperature of nearly 900°C to below 90°C using only foam materials or silicone sponge pads. The problem to be solved

[0008] The problem that the present invention aims to solve is to provide a thermal runaway prevention film that can ensure safety in the use of a lithium secondary battery by blocking the further propagation of flames in the event of a fire occurring during the use of the secondary battery.

[0009] Another objective of the present invention is to provide a secondary battery module and a secondary battery pack with excellent stability, equipped with a film that prevents the propagation of heat and flame between cells in the event of thermal runaway of high-voltage battery cells. means of solving the problem

[0011] One aspect of the present invention for achieving the above-mentioned purpose is,

[0012] The present invention relates to a thermal runaway prevention film comprising phase transition crystalline fibers of an alkali halide compound, a halide, or a phase transition inorganic compound.

[0013] The above alkali halide compound may be selected from the group consisting of LiF (lithium fluoride), LiCl (lithium chloride), LiBr (lithium bromide), LiI (lithium iodide), NaF (sodium fluoride), NaCl (sodium chloride), NaBr (sodium bromide), NaI (sodium iodide), KF (potassium fluoride), KCl (potassium chloride), KBr (potassium bromide), KI (potassium iodide), RbF (rubidium fluoride), RbCl (rubidium chloride), RbBr (rubidium bromide), RbI (rubidium iodide), CsF (cesium fluoride), CsCl (cesium chloride), CsBr (cesium bromide), CsI (cesium iodide), and mixtures thereof.

[0014] The above halides may be selected from the group consisting of TlCl (thallium chloride), TlBr (thallium bromide), TlI (thallium iodide), InCl (indium chloride), InBr (indium bromide), InI (indium iodide), SnCl2 (tin chloride (ii)), SnBr2 (tin bromide (ii)), SnI2 (tin iodide (ii)), BiCl3 (bismuth chloride (iii)), BiBr3 (bismuth bromide (iii)), BiI3 (bismuth iodide (iii)), and CuI (copper iodide).

[0015] The above inorganic compound may be selected from the group consisting of MgCl2·6H2O (magnesium chloride), Sr(OH)2·8H2O (strontium hydroxide), Ba(OH)2·8H2O (barium hydroxide), Na2S2O3·5H2O (sodium thiosulfate), CaBr2·6H2O (calcium bromide), Zn(NO3)2·6H2O (zinc nitrate), Na2HPO4·12H2O (disodium phosphate), Na2SO4·10H2O (sodium sulfate), LiNO2·3H2O (lithium nitrite), and CaCl2·6H2O (calcium chloride).

[0016] The above thermal runaway prevention film may further include a gas adsorbent inside.

[0017] The above gas adsorbent may be one or more selected from the group consisting of porous carbon materials, porous metal-organic frameworks, porous silica gel, porous zeolite, porous activated carbon alumina, and porous bauxite.

[0018] The above crystalline fibers can be arranged with directionality.

[0019] A thermal runaway prevention film characterized in that the phase transition crystalline fiber of the alkali halide compound, halide, or phase transition inorganic compound is a crystalline fiber manufactured by mixing a porous solid material into an ionic melt of the alkali halide compound, halide, or phase transition inorganic compound to prepare a slurry, then compressing and packing the slurry inside a support so as to be pore-free, and growing crystals while heating and evaporating the support in which the slurry is compressed and packed.

[0020] Another aspect of the present invention relates to a thermal runaway prevention sheet manufactured by covering both sides of the thermal runaway prevention film of the present invention described above with a support.

[0021] The above support may be one or more polymer sheets selected from the group consisting of polyvinyl chloride, cellulose acetate, polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyolefin, polymethyl methacrylate, and polyvinyl acetate.

[0022] The thickness of the above thermal runaway prevention sheet is 5 to 50 mm, and the final density is in the range of 150 to 400 kg / m³.

[0023] Another aspect of the present invention relates to a secondary battery module comprising the aforementioned thermal runaway prevention film or thermal runaway prevention sheet.

[0024] Another aspect of the present invention relates to a secondary battery pack comprising the secondary battery module of the present invention described above. Effects of the invention

[0026] The thermal runaway prevention film of the present invention is inserted into a secondary battery and blocks the propagation of flames or heat to the outside when a flame occurs inside the secondary battery, thereby minimizing additional chain reactions and damage caused by the flame generated inside the secondary battery. In this way, the thermal runaway prevention film according to the present invention can further enhance safety in a secondary battery module or secondary battery pack containing it.

[0027] The thermal runaway prevention film of the present invention maintains an optimal temperature by cooling the battery during normal operation of the battery, and prevents thermal runaway when abnormal situations such as thermal runaway occur, thereby preventing the loss of function of the entire cell contained within the module. Brief explanation of the drawing

[0029] FIG. 1 is a schematic cross-sectional view of a thermal runaway prevention film according to one embodiment of the present invention. Figure 2 is a photograph of a LiCl crystalline fiber prepared in an embodiment of the present invention. Figure 3 is a photograph of NaCl crystalline fibers prepared in an embodiment of the present invention. Figure 4 is a photograph of a KCl crystalline fiber prepared in an embodiment of the present invention. Figure 5 is a scanning electron microscope (SEM) image of a KCl crystalline fiber prepared in an embodiment of the present invention. Figure 6 shows the EDS spectrum of a KCl crystalline fiber prepared in an embodiment of the present invention. Figure 7 shows the results of X-ray diffraction (XRD) analysis of KCl crystalline fibers. Figure 8 is a photograph of an RbCl crystalline fiber prepared in an embodiment of the present invention. Figure 9 is a photograph of a CsCl crystalline fiber prepared in an embodiment of the present invention. Figure 10 is a photograph showing the results of a heat transfer experiment using KCl crystalline fibers prepared in an embodiment of the present invention. Specific details for implementing the invention

[0030] The present invention will be described in more detail below.

[0031] In order to clearly explain the invention in the drawings, parts unrelated to the explanation have been omitted, and similar parts throughout the specification have been given similar reference numerals.

[0032] In this specification, singular expressions include plural expressions unless the context clearly indicates otherwise. In this specification, terms such as "comprising" or "having" are intended to specify the existence of the features, numbers, steps, actions, components, parts, or combinations thereof described in the specification, and should be understood as not precluding the existence or addition of one or more other features, numbers, steps, actions, components, parts, or combinations thereof.

[0033] One aspect of the present invention relates to a thermal runaway prevention film comprising phase-transition crystalline fibers of an alkali halide compound, a halide, or a phase-transition inorganic compound. The crystalline fibers are highly crystallized and ordered particles, and are crystalline fibers formed in a regular three-dimensional array in space.

[0034] Phase Changing Materials (PCMs) are substances capable of absorbing, storing, and releasing heat in response to changes in ambient temperature, possessing a large amount of latent heat within a small volume. PCMs are materials that utilize the latent heat properties of absorbing or releasing heat as they undergo a phase transition. These materials absorb heat when the temperature rises and release it when it falls, depending on changes in heat flow caused by external and internal temperature gradients. By minimizing temperature fluctuations at the phase transition temperature, they enable the maintenance of an optimal temperature. The heat of dissolution of latent heat materials is an inherent characteristic of the substance; since the phase transition temperature and heat of dissolution vary by material, mixing and utilizing appropriate latent heat materials according to the intended purpose allows for effective performance over a wide temperature range.

[0035] Thermal runaway in lithium-ion batteries continuously generates heat and oxygen until all internal energy is exhausted, so it cannot be extinguished by conventional fire extinguishing equipment. The thermal runaway prevention film containing phase-transition crystalline fibers of the present invention can block thermal runaway by absorbing high heat within a golden time of 15 to 40 seconds during a lithium-ion battery fire and cooling the battery, as a phase transition phenomenon by endothermic change occurs in accordance with the temperature change of the battery cell.

[0036] The above alkali halide compounds are LiF (lithium fluoride, melting point 845°C), LiCl (lithium chloride, melting point 605°C), LiBr (lithium bromide, melting point 552°C), LiI (lithium iodide, melting point 446°C), NaF (sodium fluoride, melting point 993°C), NaCl (sodium chloride, melting point 801°C), NaBr (sodium bromide, melting point 747°C), NaI (sodium iodide, melting point 661°C), KF (potassium fluoride, melting point 858°C), KCl (potassium chloride, melting point 770°C), KBr (potassium bromide, melting point 734°C), KI (potassium iodide, melting point 681°C), RbF (rubidium fluoride, melting point 775°C), RbCl (rubidium chloride, melting point 718°C), It may be selected from the group consisting of RbBr (rubidium bromide melting point 693°C), RbI (rubidium iodide melting point 646°C), CsF (cesium fluoride melting point 682°C), CsCl (cesium chloride melting point 645°C), CsBr (cesium bromide melting point 636°C), CsI (cesium iodide melting point 621°C), and mixtures thereof.

[0037] The above halides are TlCl (thallium chloride melting point 430°C), TlBr (thallium bromide melting point 480°C), TlI (thallium iodide melting point 441°C), InCl (indium chloride melting point 586°C), InBr (indium bromide melting point 285°C), InI (indium iodide melting point 210°C), SnCl2 (tin(II) chloride melting point 247°C), SnBr2 (tin(II) bromide melting point 215°C), SnI2 (tin(II) iodide melting point 320°C), BiCl3 (bismuth(III) chloride melting point 227°C), BiBr3 (bismuth(III) bromide melting point 219°C), BiI3 (bismuth(III) iodide melting point 408°C), and It may be selected from the group consisting of CuI (copper iodide melting point 606°C).

[0038] The above inorganic compounds are MgCl2·6H2O (magnesium chloride, melting point 714°C), Sr(OH)2·8H2O (strontium hydroxide, melting point 375°C), Ba(OH)2·8H2O (barium hydroxide, melting point 78°C), Na2S2O3·5H2O (sodium thiosulfate, melting point 48°C), CaBr2·6H2O (calcium bromide, melting point 730°C), Zn(NO3)2·6H2O (zinc nitrate, melting point 110°C), Na2HPO4·12H2O (disodium phosphate, melting point 250°C), Na2SO4·10H2O (sodium sulfate, melting point 894°C), LiNO2·3H2O (lithium nitrite, melting point 222°C), CaCl2·6H2O (calcium chloride, melting point It may be selected from a group consisting of 772℃).

[0039] The thermal runaway prevention film of the present invention may further include a gas adsorbent inside. In the present invention, the method of adsorption of the gas adsorbent, whether physical or chemical adsorption, is not limited, and any material having gas absorption capability may be used without limitation. The gas adsorbent may be one or more selected from the group consisting of porous carbon materials, porous metal-organic frameworks, porous silica gel, porous zeolite, porous activated carbon alumina, and porous bauxite. Meanwhile, any one of Fe3O4, Zn2[Fe(CN)6], Zn3[Fe(CN)6]2, and Ce[Fe(CN)6] may also be used as the gas adsorbent.

[0040] The average size of the above gas adsorbent may be 5㎛ or less, preferably 3㎛ or less, and more preferably 1㎛ or less. Specifically, it may be 0.1 to 5㎛, preferably 0.1 to 3㎛, and more preferably 0.1 to 1㎛, but is not necessarily limited thereto.

[0041] In the present invention, crystalline fibers can be arranged directionally within a thermal runaway prevention film. When crystalline fibers are arranged directionally, the specific surface area increases, resulting in improved thermal conductivity and heat absorption efficiency, and the volume is reduced, allowing for a thinner fabrication.

[0042] The phase-transition crystalline fibers of alkali halide compounds, halides, or phase-transition inorganic compounds constituting the thermal runaway prevention film of the present invention are manufactured by an evaporative drying method in which an ionic substance of an alkali halide compound, a halide, or phase-transition inorganic compound is mixed with a solvent and the molten solution is heated and continuously passed through a support material to produce high-purity crystalline fibers.

[0043] Specifically, first, an ionic melt is prepared by mixing an alkali halide compound, a halide, or a phase-transition inorganic compound in a solvent. Then, a porous solid material is mixed with the ionic melt obtained in the previous step to prepare a slurry, and the slurry is compressed and packed inside a support to be pore-free. Crystalline fibers can be obtained by heating the support in which the slurry is compressed and drying it by evaporation according to a temperature and concentration gradient, thereby growing crystals.

[0044] The solvents usable for preparing the ionic melt may be one or more selected from the group consisting of alcohol-based solvents, ether-based solvents, ketone-based solvents, amide-based solvents, ester-based solvents, and hydrocarbon-based solvents.

[0045] The concentration of the ionic melt of the alkali halide compound, halide, or phase transition inorganic compound may be 5 to 40 weight%. When mixing the alkali halide compound, halide, or phase transition inorganic compound with a solvent, heating or stirring may be performed as necessary. For example, mixing may be performed at 400 rpm for 0.5 to 2 hours at room temperature or high temperature of 25°C to 70°C.

[0046] The porous solid materials for slurries usable in the present invention include silicate, sodium silicate, sodium metasilicate, lithium silicate, fumed silica, silicon dioxide, magnesium aluminum silicate, magnesium calcium silicate, aluminum calcium silicate, magnesium aluminum calcium silicate, aluminum oxide, germanium oxide, zirconium oxide, boric anhydride, activated carbon, super activated carbon, microcrystalline cellulose, cellulose fiber, zeolite, montmorillonite, and hectorite. Magadite, kenyaite, kaolinite, saponite, beidelite, nontronite, vermiculite, mica, synthetic mica, kanemite, smectite, illite, chlorite, muscovite, pyrophyllite, antigorite, glauconite, vermiculite, sepiolite, imogolite, sobockite, nacrite, anauxite, sericite, ledikite,Examples include nanoparticles composed of materials selected from the group consisting of chrysotile and antigorite, but are not necessarily limited to these.

[0047] An ionic melt is added to a porous solid material in a mixing ratio of 7:2 to 9:2 by weight and uniformly mixed at about 100 rpm to 200 rpm to produce a slurry having a viscosity of 100,000 to 200,000 cp at room temperature.

[0048] The above-mentioned support is a channel-type support that accommodates a slurry containing a porous solid material, and can be made of metal, plastic, ceramic, and / or glass, and the diameter of the support is 10 mm to 50 mm, and the length of the support is within the range of 3 to 6 cm.

[0049] In the evaporation drying step of the above-mentioned carrier, it is preferable to set the heating temperature to 25 to 100°C due to thermal diffusion that induces mass transfer of the ionic aqueous solution occurring in the fine volume pores, and to set the humidity in the evaporation drying step to 10 to 50%.

[0050] Another aspect of the present invention relates to a thermal runaway prevention sheet in which a thermal runaway prevention film described above is inserted between two supports.

[0051] FIG. 1 is a schematic cross-sectional view of a thermal runaway prevention sheet according to one embodiment of the present invention.

[0052] Referring to FIG. 1, the thermal runaway prevention sheet according to the present invention is manufactured by covering both sides of the thermal runaway prevention film (10) of the present invention described above with a support (polymer sheet) (20).

[0053] As described above, the thermal runaway prevention film (10) comprises phase transition crystalline fibers of an alkali halide compound, a halide, or a phase transition inorganic compound, and may optionally further comprise a gas adsorbent.

[0054] The above support (20) may be one or more polymer sheets selected from the group consisting of polyvinyl chloride, cellulose acetate, polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyolefin, polymethyl methacrylate, polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyimide (PI), and polyvinyl acetate.

[0055] In one embodiment of the present invention, the thickness of the thermal runaway prevention sheet is 5 to 50 mm, and the final density may be in the range of 150 to 400 kg / m³, but the present invention is not limited thereto.

[0056] To describe the method for manufacturing a thermal runaway prevention sheet according to the present invention, a hot-melt adhesive layer of 1 to 100 μm is applied between each polymer support (20) discharged from two rollers, and phase-transition crystalline fibers of an alkali halide compound, a halide, or a phase-transition inorganic compound constituting a thermal runaway prevention film (10) are placed, and then sealed by vacuum thermal compression, and if necessary, additionally sealed by a high-frequency method to manufacture a thermal runaway prevention sheet having the structure shown in FIG. 1. Since the thermal runaway prevention sheet undergoes a phase transition from solid to liquid depending on the temperature change of the battery cell, it can be manufactured in a form that is bonded to adjacent or in contact with each of the left and right sides of the sheet. When manufactured in this way, the phase-transition crystalline fibers of an alkali halide compound, a halide, or a phase-transition inorganic compound do not leak out of the sheet even if any part of the thermal runaway prevention sheet is cut. When crystalline fibers are uniformly arranged between two supports, they are spatially more uniform compared to crystalline powder, resulting in a larger specific surface area and the advantage of increased heat absorption efficiency.

[0057] Another aspect of the present invention relates to a secondary battery module comprising the aforementioned thermal runaway prevention film or thermal runaway prevention sheet.

[0058] The thermal runaway prevention film of the present invention may be included within a secondary battery module. The secondary battery module includes secondary batteries and thermal runaway prevention films. The thermal runaway prevention film is inserted between the secondary batteries to delay the transfer of heat through an endothermic reaction in the event of a fire, and exhibits a fire extinguishing function by suppressing combustion and propagation caused by the fire.

[0059] In a battery module, the thermal runaway prevention film may be located in at least one of the following: i) between one cell and an adjacent cell among a plurality of secondary battery cells housed in a housing; ii) between the electrode tab of one secondary battery cell and the electrode tab of an adjacent cell; and iii) the upper part of a cell while housed in a housing member.

[0060] A secondary battery pack may also be provided by including at least one such secondary battery module. The secondary battery pack may be manufactured by combining the said secondary battery modules as unit modules according to the desired output and capacity, and considering mounting efficiency, structural stability, etc., it may be preferably used as a power source for electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, power storage devices, etc., but the scope of application is not limited to these.

[0061] The present invention will be explained in more detail below through examples. These examples are merely for the purpose of explaining the invention more specifically, and the scope of the invention is not limited by these examples.

[0062] Examples

[0063] Example 1 (Preparation of LiCl crystalline fibers)

[0064] An aqueous LiCl solution was prepared by mixing LiCl (ACS reagent, ≥99% Sigma-Aldrich) and distilled water to an initial concentration of 20 wt% and then dissolving it in a heated stirrer at 25°C and 400 rpm. The aqueous LiCl solution was added to fumed silica with a size of 15 nm and mixed uniformly at 100 rpm to prepare a slurry with a viscosity of 100,000 to 200,000 cP at room temperature. At this time, the aqueous solution weighed 7 g and the fumed silica weighed 2 g. This slurry was introduced into a channel support filled with silica particles inside a polyethylene tube having a diameter of 15 mm and a height of 30 mm, and the support was compressed and packed to ensure there were no pores inside. The slurry-compressed carrier was placed upright in a forced convection oven with only one surface exposed, and the inside of the oven was set to a temperature of 70°C and a humidity of 20% and left for 48 hours.

[0065] Pure LiCl crystalline fibers were produced by growing crystals according to the temperature and concentration gradient for 48 hours under the above conditions. A photograph of the produced LiCl crystalline fibers is shown in Fig. 2.

[0067] Example 2 (Preparation of NaCl crystalline fibers)

[0068] Crystalline fibers were prepared in the same manner as in Example 1, except that an aqueous NaCl solution and a constant temperature and humidity chamber were used. To control the degree of evaporation diffusion through an elevated temperature and humidity environment, a carrier packed with slurry was placed upright in the constant temperature and humidity chamber with only one surface exposed. As a result of growing crystals for 48 hours with the interior of the chamber set to a temperature of 80°C and a humidity of 40%, pure NaCl crystalline fibers were prepared. A photograph of the prepared NaCl crystalline fibers is shown in Figure 3.

[0069] Example 3 (Preparation of NaCl crystalline fibers in seawater)

[0070] NaCl crystalline fibers were prepared in the same manner as in Example 2, except that 1 kg of seawater was concentrated to 20 g using a rotary evaporator instead of an aqueous NaCl solution, and a support material with a diameter of 500 mm and a length of 75 cm was used.

[0072] Example 4 (Preparation of KCl crystalline fibers)

[0073] A crystalline fiber was prepared by carrying out the same procedure as in Example 1, except that an aqueous KCl solution was used. The microstructure of the prepared KCl crystalline fiber was measured using a scanning electron microscope (SEM), and the image is shown in Figure 4.

[0074] To confirm the crystalline phase of the KCl crystalline fiber prepared in this embodiment, X-ray diffraction (XRD) analysis was performed, and the results are shown in Fig. 7. Fig. 6 is the EDS spectrum of the KCl crystalline fiber prepared in this embodiment.

[0075] As shown in Fig. 7, in the case of the KCl crystalline fiber of the present invention, peaks due to crystals appear, whereas in the case of KCl powder, it was confirmed that no crystalline phase appears other than the peaks that appear in the crystalline KCl fiber of the present invention. It can be confirmed by SEM, XRD, and EDS data that the manufacturing method of the present invention produces crystallized fibers.

[0077] Example 5 (Preparation of RbCl crystalline fibers)

[0078] A crystalline fiber was prepared by carrying out the same procedure as in Example 1, except that an aqueous RbCl solution was used. A photograph of the prepared RbCl crystalline fiber is shown in Fig. 8.

[0080] Example 6 (Preparation of CsCl crystalline fibers)

[0081] A crystalline fiber was prepared by carrying out the same procedure as in Example 1, except that an aqueous CsCl solution was used. A photograph of the prepared CsCl crystalline fiber is shown in Fig. 9.

[0083] Example 7 (MgCl 2 ·6H 2 O Crystalline fiber manufacturing)

[0084] A crystalline fiber was prepared by carrying out the same procedure as in Example 1, except that an aqueous solution of MgCl2·6H2O was used.

[0086] Example 8 (CaCl 2 ·6H 2 O Crystalline fiber manufacturing)

[0087] A crystalline fiber was prepared by carrying out the same procedure as in Example 1, except that an aqueous solution of CaCl2·6H2O was used.

[0089] Preparation Example 1: Preparation of a thermal runaway prevention film

[0090] A thermal runaway prevention film was prepared by applying a hot-melt adhesive layer of 1 to 100 μm on a polyethylene terephthalate (PET) layer as a polymer film, placing phase-transition crystalline fibers of alkali halide compounds, halides, or phase-transition inorganic compounds prepared in Examples 1 to 8, sealing by vacuum thermal compression, and then additionally sealing by a high-frequency method.

[0092] Test Example 1: Measurement of Phase Transition Temperature

[0093] To confirm the morphology of the crystalline fibers obtained in Examples 1 to 8, differential scanning calorimetry (DSC) analysis was performed on the crystalline fibers prepared in each example to observe the phase transition temperature and measure the length of the fibers, and the results are shown in Table 1 below.

[0094] molten liquid Support diameter (nm) Carrier length (cm) menstruum Concentration (wt%) Temperature (°C) RH(%) Fiber length (cm) Phase transition temperature (°C) Example 1 LiCl 15 3 distilled water 20 70 10 5 605 Example 2 NaCl 250 3 distilled water 20 80 40 6 801 Example 3 NaCl 15 3 sea ​​water 100 70 40 2 801 Example 4 KCl 15 3 distilled water 20 70 10 17 770 Example 5 RbCl 15 3 distilled water 20 70 10 4.4 718 Example 6 CsCl 15 3 distilled water 20 70 10 2.5 645 Example 7 MgCl2·6H2O 15 3 distilled water 20 90 10 3 714 Example 8 CaCl2·6 H2O 15 3 distilled water 20 70 5 5 772

[0096] As shown in Table 1 above, the crystalline fiber according to the present invention grew to a length of 2.5 cm to 17 cm, and the thermal runaway prevention film applied to the crystalline fiber manufactured according to the present invention exhibited a phase transition temperature of 605°C to 801°C, showing a characteristic that can block thermal runaway by phase transition.

[0098] Test Example 2: Heat transfer experiment of thermal runaway prevention sheet

[0099] Figure 10 is a photograph showing the results of a heat transfer experiment of a thermal runaway prevention sheet using KCl crystalline fibers prepared in Example 4. Crystalline powder and crystalline fibers were placed on a heating plate, and the rate of temperature rise was captured and compared using an infrared camera. In the photograph, yellow represents the temperature of the heating plate, and purple represents a relatively low temperature. Looking at the photograph in Figure 10, it can be confirmed that when the same amount of heat is applied, the crystalline fibers absorb heat well and exhibit effective thermal runaway prevention performance.

[0100] Although preferred embodiments of the present invention have been described in detail above, it will be understood that such embodiments are provided merely as examples. Numerous modifications, changes, and substitutions will be made by those skilled in the art without departing from the spirit of the invention. Accordingly, the appended claims are intended to include all modifications that fall within the spirit and scope of the invention.

Claims

Claim 1 A thermal runaway prevention film comprising phase transition crystalline fibers of an alkali halide compound, a halide, or a phase transition inorganic compound, wherein the phase transition crystalline fibers of the alkali halide compound, halide, or phase transition inorganic compound are crystalline fibers produced by an evaporative drying method in which an ionic substance of the alkali halide compound, halide, or phase transition inorganic compound is mixed in a solvent and the molten solution is continuously passed through a support while heating. Claim 2 A thermal runaway prevention film according to claim 1, characterized in that the alkali halide compound is selected from the group consisting of LiF (lithium fluoride), LiCl (lithium chloride), LiBr (lithium bromide), LiI (lithium iodide), NaF (sodium fluoride), NaCl (sodium chloride), NaBr (sodium bromide), NaI (sodium iodide), KF (potassium fluoride), KCl (potassium chloride), KBr (potassium bromide), KI (potassium iodide), RbF (rubidium fluoride), RbCl (rubidium chloride), RbBr (rubidium bromide), RbI (rubidium iodide), CsF (cesium fluoride), CsCl (cesium chloride), CsBr (cesium bromide), CsI (cesium iodide), and mixtures thereof. Claim 3 A thermal runaway prevention film according to claim 1, characterized in that the halogenate is selected from the group consisting of TlCl (thallium chloride), TlBr (thallium bromide), TlI (thallium iodide), InCl (indium chloride), InBr (indium bromide), InI (indium iodide), SnCl2 (tin chloride (ii)), SnBr2 (tin bromide (ii)), SnI2 (tin iodide (ii)), BiCl3 (bismuth chloride (iii)), BiBr3 (bismuth bromide (iii)), BiI3 (bismuth iodide (iii)), and CuI (copper iodide). Claim 4 A thermal runaway prevention film according to claim 1, characterized in that the phase transition inorganic compound is selected from the group consisting of MgCl2·6H2O (magnesium chloride), Sr(OH)2·8H2O (strontium hydroxide), Ba(OH)2·8H2O (barium hydroxide), Na2S2O3·5H2O (sodium thiosulfate), CaBr2·6H2O (calcium bromide), Zn(NO3)2·6H2O (zinc nitrate), Na2HPO4·12H2O (disodium phosphate), Na2SO4·10H2O (sodium sulfate), LiNO2·3H2O (lithium nitrite), and CaCl2·6H2O (calcium chloride). Claim 5 A thermal runaway prevention film according to claim 1, characterized in that the thermal runaway prevention film further comprises a gas adsorbent inside. Claim 6 A thermal runaway prevention film according to claim 5, characterized in that the gas adsorbent is one or more selected from the group consisting of porous carbon materials, porous metal-organic frameworks, porous silica gel, porous zeolite, porous activated carbon alumina, and porous bauxite. Claim 7 A thermal runaway prevention film according to claim 5, characterized in that the crystalline fibers are arranged with directionality. Claim 8 delete Claim 9 A thermal runaway prevention sheet manufactured by covering both sides of a thermal runaway prevention film according to any one of claims 1 to 5 with a support. Claim 10 A thermal runaway prevention sheet according to claim 9, wherein the support is a sheet made of one or more polymers selected from the group consisting of polyvinyl chloride, cellulose acetate, polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyolefin, polymethyl methacrylate, polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyimide (PI), and polyvinyl acetate. Claim 11 A thermal runaway prevention sheet according to claim 9, characterized in that the thickness of the thermal runaway prevention sheet is 5 to 50 mm and the final density is in the range of 150 to 400 kg / ㎥. Claim 12 A thermal runaway prevention sheet according to claim 9, characterized in that the thermal runaway prevention film and the support are additionally bonded by hot-melt bonding or high-frequency bonding. Claim 13 A secondary battery module comprising a thermal runaway prevention film as described in any one of claims 1 to 7. Claim 14 A secondary battery pack comprising the secondary battery module of claim 13.

Citation Information

Patent Citations

  • Method for producing battery cell assembly, battery cell assembly, and battery cell

    JP2023120398A

  • Ceramic product with oriented particles and method for the production thereof

    KR1020170020437A

  • Sheet for rechargeable lithium battery and rechargeable lithium battery including the same

    KR1020230142245A